TWELVE-MONTH EFFICACY OF INTRAVITREAL BEVACIZUMAB INJECTION FOR CHRONIC, ATYPICAL, OR RECURRENT CENTRAL SEROUS CHORIORETINOPATHY. Issue 1 (January 2019) - Chung, Yoo-Ri; Kim, Jong Wan; Song, Ji Hun; Park, Aram; Kim, Min Ho
Abstract : Purpose: To evaluate intravitreal bevacizumab (IVB) injection efficacy for the treatment of chronic, atypical, or recurrent central serous chorioretinopathy (CSC). Methods: Clinical data from 77 eyes of 71 patients with chronic, atypical, or recurrent CSC treated with IVB were retrospectively analyzed. After initial 6-weekly IVB administration until no subretinal fluid remained at the fovea, additional as-needed IVBs were administered, based on optical coherence tomography findings. Best-corrected visual acuity and central retinal thickness (CRT) were analyzed at baseline and 3, 6, 9, and 12 months after initial IVB. Results: The significant improvement of baseline logarithm of minimum angle of resolution best-corrected visual acuity and CRT at 3 months (both P < 0.001) was maintained throughout the 12-month follow-up period. Best-corrected visual acuity improved significantly in patients with chronic and recurrent CSC, at all time points (all P < 0.05), but not in patients with atypical CSC. The CRT reduction was significant in all subgroups during the follow-up period (all P < 0.05). Definite leakage on initial fluorescein angiography correlated with improved reduction in CRT ( P = 0.039). Conclusion: As-needed optical coherence tomography–based IVB was effective for reducing CRT in patients with chronic, atypical, or recurrent CSC, and for vision improvement in chronic and recurrent CSC over the 1-year follow-up period. Abstract : This retrospective case series showed that initial repeated and subsequent, as-needed, intravitreal bevacizumab injection was effective for anatomical and functional improvement in patients with chronic, atypical, or recurrent central serous chorioretinopathy for 12 months.